'Like an apparition': Oriental ghosting in Flaubert's Éducation sentimentale - Yee, J (Oxford University Press, 2013)
This article looks at intratextual echoes, within Flaubert's 1869 Éducation sentimentale, of his earlier novel Salammbô (1862) and the various accounts of his voyage in Egypt between 1849 and 1851 (including his notes and letters, and published accounts by his travel companion Maxime Du Camp). The manuscripts of L'Éducation sentimentale also reveal traces, later removed, of these earlier texts. Flaubert employs imagery associated with two Oriental women — the Egyptian courtesan Kuchouk-Hânem, and the fictive Salammbô herself — in building up the figure of Madame Arnoux. These recurrences predominantly concern feminine dress and accessories, as well as a certain angle of view in which the woman is seen from below, but this can be regarded as deliberate textual fetishism rather than the unconscious sexual fetishism that earlier critics have tended to emphasize. These parallels are matched by the deliberately encrypted presence, within L'Éducation sentimentale, of Flaubert's Oriental travel companion Du Camp, in the form of Monsieur Arnoux. Flaubert uses the character of Arnoux not only to settle old scores but, more importantly, as part of his own polemical attack on socially engaged art and on the industrialization of the work of art.